Development of a Reproducible Model of Murine Pneumonia with Diverse Strains of Penicillin-Resistant Streptococcus pneumoniae (PRSP) (2005)
ABSTRACT: Background: experimental murine pneumonia can be induced with most susceptible strains, but results with PRSP are much harder to reproduce. By optimizing in vitro growth of PRSP, we developed a reproducible murine model of pneumonia, useful to evaluate in vivo efficacy of antibiotics. Methods: we used 6 clinical strains of PRSP representing serotypes 19F, 9V, 14 and 6B as well as S. pneumoniae ATCC 49619 as standard strain. After optimization of culture conditions to obtain maximal growth of PRSP, neutropenic animals were infected by nasal instillation of 50 µL log-phase bacteria. MPF Udea:ICR(CD-1) female mice were 6 weeks-old and weighted 25±2g when inoculated with 10 7.7-8.4 log10 CFU/mL of each strain. Groups of 3 mice were sacrificed and their lungs removed at 1, 2, 4, 6, 12, 14, 16, 24, 36, and 48 h after infection in order to determine the dynamics of bacterial infection by appropriate homogenization, dilution, serial plating, and culture on TSA 5% blood agar. A second model, in which 50% of the inoculum was replaced by 10% porcine mucin, was similarly evaluated. Results: culture optimization led to growth of 9-10 log10 CFU/mL, avoiding autolysis. One hour after infection, mice had 6.20-7.79 log10 CFU/g of lung, a count that decreased to 3.6-7.6 log10 CFU/g at 17±5 h (nadir) and then increased up to 6.8-9.6 log10 CFU/g at 42±6 h (zenith), giving a net growth of 2.0-3.2 logs in 25 h. Histopathology confirmed pneumonia in all animals with all PRSP strains, but most mice recovered from the infection after 5 days. Mucin enhanced the virulence of all PRSP strains by transforming the model into a uniformly lethal pneumonia by 29 to 79 hours, with bacterial dissemination to all vital organs. Conclusion: reproducible induction of PRSP pneumonia was attained with diverse clinical strains. Virulence enhancement with 10% porcine mucin allowed a lethal pneumonia model.